2019
DOI: 10.1186/s12884-019-2543-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surgical evacuation on pregnancy outcomes of subsequent embryo transfer cycle following miscarriage in an initial IVF cycle: a retrospective cohort study

Abstract: BackgroundIt is still uncertain whether surgical evacuation adversely affects subsequent embryo transfer. The present study aims to assess the influence of surgical evacuation on the pregnancy outcomes of subsequent embryo transfer cycle following first trimester miscarriage in an initial in vitro fertilization and embryo transfer (IVF-ET) cycle.MethodsA total of 645 patients who underwent their first trimester miscarriage in an initial IVF cycle between January 2013 and May 2016 in Nanjing Drum Tower Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Ozgur et al suggested that women who underwent surgical management for CPL may require 6 months for endometrial functional recovery to optimize the chance of achieving a live birth after FET. A previous study reported that there was no notable difference in pregnancy outcomes of subsequent embryo transfer for women who underwent surgical evacuation compared with those who did not . Surgical evacuation may lead to endometrial damage because of potential complications such as infection and intrauterine adhesion, and thus may play a causal role in endometrial thinning that is closely associated with unfavorable pregnancy outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozgur et al suggested that women who underwent surgical management for CPL may require 6 months for endometrial functional recovery to optimize the chance of achieving a live birth after FET. A previous study reported that there was no notable difference in pregnancy outcomes of subsequent embryo transfer for women who underwent surgical evacuation compared with those who did not . Surgical evacuation may lead to endometrial damage because of potential complications such as infection and intrauterine adhesion, and thus may play a causal role in endometrial thinning that is closely associated with unfavorable pregnancy outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that there was no notable difference in pregnancy outcomes of subsequent embryo transfer for women who underwent surgical evacuation compared with those who did not. 29 Surgical evacuation may lead to endometrial damage because of potential complications such as infection and intrauterine adhesion, and thus may play a causal role in endometrial thinning that is closely associated with unfavorable pregnancy outcomes. 30 , 31 In our study, women with an IPI of 6 to 12 months were more likely to undergo surgical evacuation of the preceding CPL and were more likely to have an endometrial thickness of less than 8 mm before FET compared with those with shorter IPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Some embryos were cultured to the blastocyst stage. Blastocyst formation was determined by progression to the blastocyst stage on days 5, 6 or 7 [ 16 ]. For patients who opted to use preimplantation genetic testing for aneuploidy (PGT-A), the embryos were biopsied at the blastocyst stage.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrent miscarriage (RM) refers to cases where three or more recurrent miscarriages occur before the twentieth week of pregnancy [ 1 ]. According to the World Health Organization (WHO), RM refers to the expulsion or death of a fetus weighing less or more than 500 grams within the 20 th to 24 th week of pregnancy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%